Coloración Psicodélica de Imágenes Digitales mediante Lógica Difusa - Castro, Linda Sheriyn Rodríguez; Fajardo, Iván Javier Ponce; Cuchango, Helbert Eduardo Espitia (Ingeniería, 2013)
This paper proposes a fuzzy inference system for color manipulation in digital images in order to modify image artistic style. This manipulation generates a different color scheme that differs from that of the original image and produces a new visual feeling. Color modifi cation is achieved through a fuzzy-logic system composed of fuzzy sets and rules. The study considers an art form known as psychedelic art, generating (as a result) images whose colors cause similar effects. In the second part of this report, the system is optimized by using empirical data gathered from a panel of art experts in order to enhance the color map of the artistic style. Through different test cases, the results obtained by the system before and after optimization are shown.